Предмет: Алгебра,
автор: лилил5
упростите выражения а(в-3)+(3-в)-в(3-в)
Приложения:
![](https://files.topotvet.com/i/d88/d88d97fe2957092df6b0b22c664ee7de.jpg)
Ответы
Автор ответа:
0
a(b-3)+(3-b)-b(3-b)=(b-3)*(a-1+b)=ab-b+b²-3a+3-3b=ab-4b+b²-3a+3
5(a-b)²-(a+b)(b-a)=5a²-10ab+5b²-b²+a²=6a²-10ab+4b²
a(a-b)²-(b-a)³=a³-2a²b+ab²-b³+3ab²-3a²b+a³=2a³-5a²b+4ab²-b³
5(a-b)²-(a+b)(b-a)=5a²-10ab+5b²-b²+a²=6a²-10ab+4b²
a(a-b)²-(b-a)³=a³-2a²b+ab²-b³+3ab²-3a²b+a³=2a³-5a²b+4ab²-b³
Похожие вопросы
Предмет: Английский язык,
автор: shestakovstas1994
Предмет: Математика,
автор: lanamilana943
Предмет: История,
автор: alinazhulkasheva
Предмет: Математика,
автор: капомоги